PENGARUH MODAL SENDIRI DAN ASET TERHADAP PEROLEHAN SISA HASIL USAHA PADA KOPERASI SIMPAN PINJAM SWASTIKA MATARAM - Wayan Wirastini; Baiq Desthania Prathama; Erviva Fariantin (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
The purpose of this study is to examine the impact of equity and assets on net income. This research is a case study on KoperasiSimpanPinjam Swastika Mataram. Equity (X1) and assets (X2) are used in this study as independent variables and net income (Y) as dependent variable. The type of this study is associative research using a quantitative approach. The associative research aims to determine the effect of equity and assets on net income partially, simultaneously and dominantly. The data were collected for 5 years (2013-2017) and were analyzed using multiple linear regression analysis (available on SPSS version 22 program) by performing partial (t) test and simultaneous (f) test. The results of this study show several findings. First, equity has a significant impact on net income partially, but assets does not. Second, equity and assets have a significant impact on net income simultaneously. Third, equity has more dominant impact on net income than assets.